2015
DOI: 10.1186/s40738-015-0005-2
|View full text |Cite
|
Sign up to set email alerts
|

Potential causes of subfertility in patients with intramural fibroids

Abstract: BackgroundIntramural leiomyomas have been long debated as a potential cause of infertility and pregnancy loss.FindingsPrevious research has linked intramural fibroids to defective implantation, as well as to abnormal peristaltic events of the uterine smooth muscle. Previous reports describe the effects of intramural fibroids on normal human fertility and early pregnancy loss, specifically in regards to implantation failure.Conclusion A thorough understanding of prior research may direct new research focus, lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 62 publications
0
17
0
Order By: Relevance
“…Similarly, uterosalpingography, and more recently cine-MRI, have shown that in infertile women, instead of normal cervix-to-fundal peristalsis at ovulation, the waves are reversed or irregular, thereby preventing sperm from fertilising the egg. Moreover, it is believed that the presence of fibroids is also a key factor in disrupting uterine peristalsis ( Pier and Bates, 2015 ). Furthermore, in some species, producing multiple embryos, regular, standing peristaltic waves may be responsible for spacing of the embryos within the uterus.…”
Section: Physiology Is More Than Molecules Eg Uterine Peristalsismentioning
confidence: 99%
“…Similarly, uterosalpingography, and more recently cine-MRI, have shown that in infertile women, instead of normal cervix-to-fundal peristalsis at ovulation, the waves are reversed or irregular, thereby preventing sperm from fertilising the egg. Moreover, it is believed that the presence of fibroids is also a key factor in disrupting uterine peristalsis ( Pier and Bates, 2015 ). Furthermore, in some species, producing multiple embryos, regular, standing peristaltic waves may be responsible for spacing of the embryos within the uterus.…”
Section: Physiology Is More Than Molecules Eg Uterine Peristalsismentioning
confidence: 99%
“…Computer simulations revealed that asymmetric contractions between the anterior and posterior walls of the uterus may lead to infertility due to transport of the blastocyst to a nonfundal site of implantation or prohibition of contact between the blastocyst and the endometrium during the window of implantation . Recent studies reported direct link between abnormal uterine peristalsis due to uterine fibroids and decreased pregnancy rate …”
Section: Uterine Disease Development and Infertilitymentioning
confidence: 99%
“…2 Recently, data are beginning to accrue suggesting adverse effect of fibroids on implantation by alteration of molecular markers of endometrial receptivity. [3][4][5] While reports available in literature are suggestive of definite detrimental effect of submucosal fibroids on endometrial receptivity, only a few reports are available which have demonstrated a negative impact of noncavity-distorting intramural fibroids on molecular mediators of endometrial receptivity. 5,6 Favorable impact of intramural myomectomy on receptivity markers and pregnancy outcome has recently been reported.…”
Section: Introductionmentioning
confidence: 99%